IMF Committee on Balance of Payments Statistics : Annual Report 2011. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2011)
The Annual Report of the IMF.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet